Teachers’ and Primary School Pupils’ Views on Content and Language Integrated Learning: The Model of Helsinki - Holmberg, Marika (My University, 2023)
This study focuses on the perceived benefits and disadvantages of content and language integrated learning by teachers and pupils at a primary school in Helsinki, Finland. Another aim was to find out how aware the teachers and pupils are of the CLIL program at their school. While CLIL has been extensively researched, most of the studies have focused on the learners’ academic achievements or the affective evidence from older learners. Primary school aged children have been studied less. In addition, with CLIL being a flexible and versatile term, the studies are rarely generalizable and thus CLIL should be actively researched in its different forms and contexts. The data in this study were collected through semi-structured interviews and short questionnaires for the pupils. Five teachers and 13 fifth and sixth-graders were interviewed. The data were analyzed using a qualitative content analysis. The findings suggest most of the teachers and pupils view the CLIL program of their school, language enriching, positively. The benefits found in the study included enjoyment for both pupils and teachers, perceived improvement of the pupils’ linguistic skills, increased motivation towards the content subject and encouragement towards using the language. The disadvantages included CLIL sometimes impacting the content learning negatively and lack of time and systematic implementation, which sometimes led to negative feelings. The teachers were aware of the basic principles of CLIL, but not of all of its pedagogical intentions. Some of the pupils were familiar with the concept of CLIL while others were not, which may be because of the perceived scarceness of CLIL lessons mentioned by both pupils and teachers. While many of the findings are in line with previous studies, the results of this study are not generalizable. Future research ideas might be investigating the differences in the experiences of CLIL class teachers who have a background of teaching English and those who do not, finding out more about the benefits and disadvantages of CLIL in this particular context by including for example learning results in multiple schools, and comparing this program to other CLIL programs to develop it further.
Keywords: Content and language integrated learning, CLIL, language enriching